Association Between Dietary Fiber Intake and Risk of Depression in Patients With or Without Type 2 Diabetes - Yafei Mao; Xinyuan Li; Shumin Zhu; Yulan Geng (Frontiers in Neuroscience, 2022)
BackgroundDepression and type 2 diabetes (T2D) are both serious public health problems, with morbidity and mortality in people increasing year by year, resulting in a heavy economic burden. A correlation between dietary fiber and both has been reported. Nevertheless, few data are available concerning dietary fiber and the risk of depression with or without T2D, which deserve further attention.Materials and MethodsWe assessed the relationship between dietary fiber intake and risk of depression with or without T2D in the 2007–2014 National Health and Nutrition Examination Survey (NHANES) population. A 24-h dietary review was used to assess fiber intake. The Patient Health Questionnaire-9 was used to assess depression. Stability of the results was assessed using restricted cubic spline models and logistic regression, as well as sensitivity analyses.ResultsA total of 17,866 adults aged 20 years and older with a mean age of 49.3 ± 17.7 years were included in this study, of whom 49.5% were male. After adjusting for covariates, the association of dietary fiber intake with the risk of depression appeared to differ between non-T2D group and T2D group (OR, 0.987; 95% CI, 0.979–0.995 vs. OR, 1.003; 95% CI, 0.988–1.017). Furthermore, when dietary fiber was converted to a categorical variable, there was evidence of interaction between T2D status and fiber intake on decreasing the prevalence of depression (P-value for interaction = 0.015). Sensitivity analysis showed stable results.ConclusionOur findings indicated that whether a patient has T2D may affect the relationship between dietary fiber intake and the risk of depression, which still needs to be confirmed by further randomized controlled trials.